Training on adequate use of opioid analgesics in West and Central Africa: a neglected step on the way to access to essential medicines? - Serena Frau; Anselme Mubeneshayi Kananga; Jackie Ndona Kingolo; Ghislaine Mbelu Kanyunyu; André Katele H. Zongwe; Aaron Nshindi Tshilengi; Raffaella Ravinetto (Taylor & Francis Group, 2021)
Alleviating acute and chronic pain is a moral imperative for health professionals and health systems, and it requires adequate access to and use of essential opioid analgesics. However, this is still a neglected issue in global health, with striking inequalities in opioids availability between high and low- and middle-income countries. Countries most affected by lack of access are those with a fragile political situation and weak regulatory and healthcare systems. The main threats to accessibility, availability and affordability are situated at different levels: legislation and policy, financing, knowledge and cultural behavior, erroneous beliefs, and training and education. Among these threats, the lack of (adequate) training and education seems to be a cross-cutting issue. Exploring the current body of knowledge about training and educational activities related to use of opioid analgesics and palliative care, is helpful to understand gaps and to delineate priorities for setting up adequate interventions. When applied to West and Central Africa, this exercise reveals that there is little information (easily) available in the public domain. The African Palliative Care Association (APCA) appears to be the leading provider of capacity building activities in this region for key stakeholders, including national authorities, healthcare professionals and the general population; it is also very active in publishing and communicating about these issues. However, apart from APCA, there is little information on training programs' contents and long-term outcomes. Furthermore, trainings rarely target important stakeholders such as lawmakers, regulators, supply officers and the lay public (i.e., patients, caregivers, community leaders and members of the society as a whole). Hence, it is urgent to fill the existing gaps in training and educational activities to improve access to essential opioid analgesics in West and Central Africa, involving different stakeholders at the national and regional level. Furthermore, such experiences should be published and made publicly available to allow for mutual learning and further upscale.